Self Care Behaviors in Patients after Myocardial Infarction - Maryam Niakan; Ezat Paryad; Farzaneh Shekholeslam; Ehsan Kazemnezhad Leili; Mohammad Assadian Rad; Hamid Reza Bonakdar; Shahnaz Bouraki (Journal of Holistic Nursing and Midwifery)
Introduction: One of determining and effective factors in health maintenance and prevention of progression of signs and symptoms of disease after heart attack is self care behaviors. The self care behaviors which can start after passing the acute period of disease has special importance in health maintanance and its recurrence.